(untitled) (Research, Society and Development, 2020)
Objective: To know the care strategies for maintaining the lives of adolescents with special health needs from the discourse of family members/caregivers. Methodology: Qualitative, descriptive research with data collection carried out in medical records and semi-structured interviews with 35 family members/caregivers of adolescents using the outpatient clinic of a university hospital. The interviews were subjected to double transcription and later discourse analysis in the Pecheutian current. Results: The family members’ discourse emphasized the care demands required by the adolescents and the strategies for maintaining life. Many families needed to restructure themselves in favor of care, adapt the family’s daily activities and travel a long itinerary in search of specialized care. Conclusions: Life-sustaining strategies refer to daily care, performing hygiene activities, using medicines correctly, taking care of food, clothing, performing blood tests and bladder catheterization. It is believed that the bond with professionals and health education are essential strategies for the continuity of care with a view to the integral care of these adolescents and their families.